Pulsed Stimuli Elicit More Robust Multisensory Enhancement than Expected - Bach, Eva C.; Vaughan, John W.; Stein, Barry E.; Rowland, Benjamin A. (Frontiers in Integrative Neuroscience, 2018)
Neurons in the superior colliculus (SC) integrate cross-modal inputs to generate responses that are more robust than to either input alone, and are frequently greater than their sum (superadditive enhancement). Previously, the principles of a real-time multisensory transform were identified and used to accurately predict a neuron’s responses to combinations of brief flashes and noise bursts. However, environmental stimuli frequently have more complex temporal structures that elicit very different response dynamics than previously examined. The present study tested whether such stimuli (i.e., pulsed) would be treated similarly by the multisensory transform. Pulsing visual and auditory stimuli elicited responses composed of higher discharge rates that had multiple peaks temporally aligned to the stimulus pulses. Combinations pulsed cues elicited multiple peaks of superadditive enhancement within the response window. Measured over the entire response, this resulted in larger enhancements than expected given enhancements elicited by non-pulsed (“sustained”) stimuli. However, as with sustained stimuli, the dynamics of multisensory responses to pulsed stimuli were highly related to the temporal dynamics of the unisensory inputs. This suggests that the specific characteristics of the multisensory transform are not determined by the external features of the cross-modal stimulus configuration; rather the temporal structure and alignment of the unisensory inputs is the dominant driving factor in the magnitudes of the multisensory product.